Consumer awareness and search trends for agrifood products certified with European Quality Schemes: PDO, PGI, and TSG - An analysis through Google Trends - Alexandra-Ioana GLOGOVEȚAN; Dan-Cristian DABIJA; Cristina Bianca POCOL (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2023)
This groundbreaking study leverages Google Trends to probe into consumer awareness of Romanian food products certified under European quality schemes, Protected Designation of Origin (PDO), Protected Geographical Indication (PGI), and Traditional Specialty Guaranteed (TSG), delivering prompt insights and addressing an existing research void. By adopting an innovative methodology through big data analytics - Google Trends and analyzing 12 sets of search terms, this study brings fresh insights to academic discourse and provides valuable information for marketers and policymakers. Prominent search interest was detected for 'Salam de Sibiu', ‘Plăcintă dobrogeană', and 'Magiun de prune Topoloveni', pointing to significant consumer familiarity. The study also unveiled regional search patterns, signifying location-based preferences, and potential marketing prospects. However, a marked contrast was found between the high interest in the products and the relatively low awareness of their European quality labels, highlighting a need for enhanced communication initiatives around these certifications. The study could be limited by its focus on Romanian certified food products, which may not be applicable to other geographical contexts. Future research endeavours may also seek to integrate data from Google Trends data with additional indicators of consumer behaviour.